Description of two new and six known species of the genus Tylencholaimus de Man, 1876 (Nematoda: Dorylaimida) with a diagnostic compendium and key to species - Ahad, Sumaya; Ahmad, Wasim (Zootaxa, 2016)
Two new and six known species of the soil-inhabiting nematode genus Tylencholaimus de Man, 1876 are described and illustrated. Tylencholaimus arakii sp. n. is characterized by having 0.56–0.65 mm long body; lip region cap-like, set off by a shallow constriction; labial disc present; odontostyle 7–8 µm and odontophore 7–8 µm long, with well-developed, asymmetrical basal knobs; total spear length 15 μm; pharynx with slender anterior part which expands abruptly into the cylindrical basal bulb occupying about 45–47% of total neck length; female genital system mono-prodelphic; transverse vulva and short, hemispheroid tail. Tylencholaimus ladakhiensis sp. n. is characterized by having 0.56–0.73 mm long, slender body; lip region cap-like, set off by a slight constriction; amphid aperture slit-like; odontostyle slender 7–9 µm, with comparatively narrow lumen, odontophore 8–9 µm long; pharynx with slender anterior part which expands abruptly into the cylindrical basal bulb, occupying about 38–45% of total neck length; female genital system didelphic-amphidelphic and rounded-conoid tail, with distinct terminal caudal pore. Tylencholaimus proximus Thorne, 1939; Tylencholaimus mongolicus Andrássy, 1967; Tylencholaimus vulvulatus Rahman, Jairajpuri, Ahmad & Ahmad, 1987; Tylencholaimus ibericus Peña-Santiago & Coomans, 1994; Tylencholaimus imperanus Mohilal & Dhanachand, 2003 and Tylencholaimus cosmos (Dhanam & Jairajpuri, 1999) Peña-Santiago, 2008 are redescribed. Tylencholaimus proximus and Tylencholaimus mongolicus are reported for the first time from India and a male is reported for the first time for T. imperanus. A diagnostic key and compendium to species of the genus Tylencholaimus is provided.